Towards an Islamic Paradigm of the Information Society - Baghestan, Abbas Ghanbari (2009)
The main purpose of this study was to understand how Muslim Communication Scholars think about the phenomenon of "information society". The study was carried out through three research questions: 1) What is the concept of information society from the perspective of Muslim Communication Scholars? 2) How could Muslim countries achieve that information society and through which process? 3) What are the similarities and differences between Muslim and Western scholars‘ opinions about the concept and process of information society? These questions aim to determine how Muslim Communication Scholars conceptualize the information society and what characteristics and components it must have to be suitable for Muslim countries. Due to the nature of the study, a qualitative research method was used by the researcher to investigate on how Muslim Communication Scholars think about the phenomenon of information society. Among the qualitative research methods, because of the nature of research problem, "grounded theory" was used in this study. Data was gathered from eleven Muslim Communication Scholars in the field of communication who had fulfilled the criteria of sampling procedure. Respondents were selected through "snowball and chain" strategy. The data collection method employed was mainly in-depth interview with the respondents. All interviews were taped recorded, transcribed verbatim and analyzed. In addition, document analysis was also carried out. The validity of study was ensured through identifying the research biases, triangulation, members‘ checks, and peer examination. The reliability was ensured through stating the researcher‘s position, triangulation and audit trail. The findings of this study yielded new characteristics, components and structure of Muslim Communication Scholars‘ perspective that are no similar to what so called "information society" in the West. Eleven major themes and several sub-themes emerged from this study in relation to Muslim Communication Scholars' conceptualizing of information society. Two themes were regarding question No.1 that are: 1) Strategy of Domination and 2) Building Islamic Civil Society. And also nine themes were found regarding question No.2, including: 1) Predominant of Knowledge, 2) Highly Educated, 3) Regulated Flow of Information, 4) Controlled Information and Communication, 5) Logical Freedom of Expression, 6) Participatory Political System, 7) Free Access to Right Information, 8) Bridged Digital Gap and 9) Maintaining Traditional Culture. According to the above themes, it was discovered that Muslim Communication Scholars conceptualize this phenomenon much different from their counterparts in the West. This study concludes that based on the findings, new model of society with different structures, components and characteristics are needed for contemporary Muslim countries. Therefore, based on their argument, the paradigm of "information society" should be changed to paradigm of "Islamic Civil Society" to be suitable for Muslims. However, as Islamic Civil Society is broader concept suggested by respondents of this study as an ideal society for contemporary Muslim countries, only its components related to the area of communication and information was discussed in this study. Specific implications and recommendation for future research are also suggested.